The Game Between Game Theory and Gaming Simulations: Design Choices. (April 2019) - Roungas, Bill; Bekius, Femke; Meijer, Sebastiaan
Background. The abstraction of complex systems, which is required by default when modelling gaming simulations, is a convoluted and time-consuming process. For gaming simulations to be efficient and effective, the problem of the real system they imitate needs to be narrowed down and simplified as much as possible. Additionally, even after abstraction of the real system, multiple design decisions need to be made and these may differ depending on the gaming simulation. Aim. This article proposes a framework for formalizing, and consequently standardizing, expediting and simplifying, the modelling of gaming simulations. Method. The proposed framework appliesgame concepts pertaining togame theory in the abstraction of the real system and thegame design decisions . Results. Application of the framework in three case studies reveals several advantages of incorporating game theory into game design, such asformally defining the game design elements andidentifying the worst-case scenarios in the real-systems, to name but two. Conclusions. Given the framework's advantages in general, and the game design recommendations it offers in particular, it is safe to conclude that, for the cases presented in this article, the framework make positive contributions towards the development of gaming simulations.